1997
DOI: 10.1097/00007632-199706150-00019
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intravenous Premarin to Decrease Postoperative Blood Loss After Pediatric Scoliosis Surgery

Abstract: Administration of Premarin resulted in a 37% decrease in the volume of postoperative drainage (mL/kg) without complications. Premarin appears to be effective in decreasing postoperative blood loss in a pediatric postoperative spinal population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…41 In another study, the use of conjugated oestrogens was associated with a 37% reduction in postoperative bleeding after paediatric scoliosis surgery. 94 Conjugated oestrogens are well tolerated and side-effects are negligible or absent. Since no more than five to seven daily doses are recommended, adverse effects due to oestrogenic hormonal activity are usually avoided.…”
Section: Conjugated Oestrogensmentioning
confidence: 99%
“…41 In another study, the use of conjugated oestrogens was associated with a 37% reduction in postoperative bleeding after paediatric scoliosis surgery. 94 Conjugated oestrogens are well tolerated and side-effects are negligible or absent. Since no more than five to seven daily doses are recommended, adverse effects due to oestrogenic hormonal activity are usually avoided.…”
Section: Conjugated Oestrogensmentioning
confidence: 99%
“…Extensive bleeding may lead to rapid fatal consequences and to risks associated with allogenic blood transfusion [4, 8, 36,40,81]. Measures should be taken to minimise these risks [18, 26,50,58,64,65,66,68,79].…”
Section: Introductionmentioning
confidence: 99%
“…The most common include drug therapy (desmopressin [2,58], aprotinin [25,85], tranexamic acid [27,65], hypotensive anaesthesia [59,83], and autotransfusion techniques, such as normovolemic acute hemodilution [14,19,56,67], perioperative salvage [3,28,56], postoperative salvage and autologous blood donation (ABD) [39,49,57,64,80,88]. During the 1990s a new drug, recombinant human erythropoietin (rHuEPO), was added to the repertory of blood-conservation techniques [6,9,32,33,73].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a controlled study McCall et al [86] have reported the efficacy of conjugated oestrogens (Premarin, WyethAyerst) in decreasing the postoperative drainage volume in adolescents having undergone deformity surgery. There were no side effects.…”
Section: Oestrogens: Estriol Conjugated Oestrogensmentioning
confidence: 99%